Book review: David Welch. Germany and Propaganda in World War One: Pacifism, Mobilization and Total War. London: I.B. Tauris, 2014. ISBN: 978-17-80-76827-4. Pp. xii, 384. Paperback. £16.99/ $28.00. Issue 5 (2015) - Colley, Thomas
No abstract available